MODIFIKASI PERSAMAAN QUATERNION PADA ALGORITMA INS UNTUK APLIKASI ROKET - Romi Wiryadinata; Wahyu Widada (National Institute of Aeronautics and Space - LAPAN, 2010)
INS algorithm is used to transform the body frame to the inertial frame of the rocket trajectory. The motion of rocket rotation is different from the air plane. The rocket has a faster motion and need a high speed computation. The pitch angle (θ) which is being greater than 90º, there will be a problem and it needs the Quaternion equation to solve the problem. In this study, the Quaternion parameters are always normalized with the same value at the time of initial initialization. The results of this study indicate that the calculation of body frame and inertial frames have similar results and showed accuracy between 0.2 - 1 meter. In the process algorithms in real-time INS will require a high-speed microprocessors to speed up the computing time on an embedded system payload. Keywords: Inertial Navigation System, Inertial Measurement Unit, Quaternion, Rocket